Penguatan Dewan Etik dalam Menjaga Keluhuran Martabat Hakim Konstitusi - Wiryanto, Wiryanto (Jurnal Konstitusi, 2016)
The Birth of the Board of Ethics of the Constitutional Judges cannot be separated from the effort to uphold a code of ethics and maintain of the dignity of the constitutional judges. Abuse of authority in the judiciary has led to the destruction of the legal system and the non-fulfillment of a sense of justice. Judicial mafias has destroyed the foundation of the authority of the judiciary and undermine the honor and dignity of judges, therefore it is necessary to take concrete measures to restore the authority of the judiciary and maintaining the honor of judges as the main pillars of the judiciary in enforcing law and justice. One concrete step is the need for strengthening the supervisory system of ethics against constitutional judges, the results of which will provide input to the Constitutional Court, whether the monitoring system of ethics against constitutional judges applied so far has been able to maintain the honor, dignity, and constitutional justices, and whether the system has provided legal certainty in its enforcement against violations of the Code of Ethics and Conduct of Constitutional Judges. Strengthening the role of the board of ethics of constitutional judges as guardians of constitutional judges dignity can be constantly improved by opening access to complaints from the public against allegations of ethical violations committed by constitutional judges.